The deep historical roots of industrial culture and regional entrepreneurship: A case study of two regions - Michael Fritsch; Maria Greve; Michael Wyrwich (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2022)
We describe and compare the development trajectories of two German regions, South Saxony and Mecklenburg, with a special focus on entrepreneurship and innovation. South Saxony has a long history of self-employment and knowledge generation that results in a persistent culture of innovative entrepreneurship. In Mecklenburg, such a culture did never emerge. Differences between the entrepreneurial ecosystems in the two regions especially pertain to the level of knowledge production and its link to new business formation in innovative and knowledge-intensive industries.
Keywords: L26; M13; O1; O3; R11; 330; Entrepreneurship; entrepreneurial ecosystems; economic history; culture; regional development